Epidemiological characteristics and pregnancy outcomes of gastroschisis in Alabama - Voleti, Sidhu Rao Surya; Cagle, Izza (International Journal of Contemporary Pediatrics, 2024)
Background: Gastroschisis is a congenital defect where an infant's intestines extend outside the body through a hole near the belly button, requiring immediate surgery post-birth. Understanding its risk factors is crucial for prevention and improving outcomes. This study aimed to describe the epidemiological trends, maternal and infant characteristics, and identify significant risk factors for gastroschisis using a comprehensive dataset and advanced statistical methods. Methods: A population-based, retrospective, age, and race-matched case-control study was conducted using Alabama birth certificate data. The study included infants born to non-Hispanic African American and non-Hispanic white mothers. Data preparation involved filtering for singleton births and excluding other congenital anomalies. Logistic regression identified significant predictors, addressing multicollinearity using the Variance Inflation Factor (VIF). Results: The dataset included 100 cases and 300 controls. Significant predictors identified through logistic regression included young maternal age (less than 20 years) (OR, 2.81; CI, 1.4-5.33), maternal smoking pre-pregnancy (OR, 1.90; CI, 1.01-3.54) and during pregnancy (OR, 2.11; CI, 1.12-3.98), and lower maternal BMI (OR, 0.92; CI, 0.88-0.96). Maternal smoking and young maternal age were significant risk factors, while maternal obesity appeared protective. Conclusions: This study identified maternal smoking, maternal BMI, and young maternal age as significant predictors of gastroschisis. These findings contribute to understanding the etiology of gastroschisis and highlight the importance of targeted interventions for at-risk populations. Further research is needed to explore underlying mechanisms and develop effective prevention strategies.